Gas chromatography-mass spectrometry analysis of phytocomponents of sargassum polycystum - Zamimi, Nurul Najwa; Ab. Halim, Noorhazayti; Darnis, Deny Susanti; Lestari, Widya; Md Mustafa, Md Muziman Syah (2019)
Sargassum polycystum is a brown seaweed, which has been reported to contain various phytoconstituents especially antimicrobial properties. However, the study on phytochemical components and biological activities of S. polycystum are yet fully understood. Therefore, the objectives of this study are to evaluate the best extraction solvents for S. polycystum and to determine the percentage of phytocomponents obtained in the n-hexane, dichloromethane (DCM) and methanol extracts of S. polycystum via Gas Chromatography-Mass Spectrometry (GC-MS) analysis. S. polycystum was collected from the coastal area of Sabah, Malaysia. After collection, it was rinsed, dried and extracted with n-hexane, DCM and methanol by soxhlet extraction. The fatty acid compounds (FAME) analysis was done using The Perkin Elmer Turbo Mass Spectrometer. This study showed that methanol is the most efficient solvent as it produced the highest extraction yield with 3.83%, followed by n-hexane with 1.69% and lastly DCM with 0.59% in S. polycystum. On top of that, this study has found 19 phytocomponents in all extraction methods of S. polycystum, which have been proven to possess antibacterial constituents such as palmitic acid, myristic acid, oleic acid, pentadecanoic acid and behenic acid as assessed by GC-MS analysis.